Dietary androgen 'supplements': separating substance from hype - Earnest, C. P. (The Physician and Sportsmedicine, 2001)
Recent advances in nutritional supplements have been used to aid athletic performance. Spurred by the popularity and financial success of creatine sales, athletes and supplement companies alike seek to find the next breakthrough product. Prominent among the new supplements are androgen prohormones, a class of steroid-mimicking products. Although many physicians and scientists view these supplements as potentially dangerous cousins to anabolic steroids, users see them as a means of obtaining steroid-like results with fewer adverse effects. The current literature reveals that thus far the androgen prohormone supplements tested do not enhance performance, body composition, or various parameters associated with good health.